On average edge length of minimum spanning trees - Nath, Suman Kumar; Chowdhury, Rezaul Alam; Kaykobad, M. (Information processing letters, 1999)
This paper presents a theorem that asserts that average edge length of the minimum spanning tree of a complete graph on n+1 vertices is less than or equal to the average edge length of all the n+1 minimum spanning trees of the induced graph on n vertices. The result is also in compliance with results given by Frieze and Steele.